MODIFIER OF PROLONGED OPERATION - L. Z. Pisarenko; N. A. Svidunovich; D. V. Kuis (Литьë и металлургия)
The modifier of cast iron, which provides the improvement of the structure and characteristics of castings, has increased duration of working, keeps the structural heredity after refining of modified cast iron, is developed.